VD_FINDINFO HC / 2011 / 697 vom 19. Dezember 2011 - VD Tribunal cantonal (2011)
DÉCISION D'IRRECEVABILITÉ, CONCLUSIONS, NATURE RÉFORMATOIRE | 132 al. 1 CPC (CH), 143 al. 1 CPC (CH), 148 CPC (CH), 56 CPC (CH)